Assessment of the effects of NPK fertilizer on edible yield and agro-biological parameters in a cowpea–amaranth intercrop - Mndzebele, B.; Ncube, B.; Fessehazion, M.; Mabhaudhi, Tafadzwanashe; Modi, Albert Thembinkosi (Frontiers Media, 2023)
Introduction: Estimates indicate that food and nutritional demand in sub-Saharan African nutrient-poor soils will exceed the high population demand. Vegetables such as amaranth and cowpea are key in contributing to food and nutritional security. Fertilizers are used to mitigate low nutrient levels in soils. This study aimed to investigate the yield parameters of cowpea and amaranth vegetables. Methods: The experiment was designed with a 2 × 4 factorial treatment structure in a completely randomized design, with intercropping and fertilizer level as treatment factors and with four replications. Results and discussion: The biomass of amaranth and cowpea increased with increased fertilizer application up to the level of 100% nitrogen, phosphorus, and potassium (NPK) fertilizer. A measure of land utilization showed values greater than one. Crop comparison showed that cowpea was more aggressive, had higher actual yield loss, and was highly competitive compared to amaranth. More income could be obtained from intercropping. The research shows the benefits of fertilizer application in improving the biomass of amaranth and cowpea. Overall, the application of NPK fertilizer at levels up to 100%, based on the results of this study, resulted in higher biomass accumulation and improved intercropping indices.